Investigation of internal conversion anomalies in 234Pa - I. N. Vishnevsky; S. S. Drapey; V. A. Zheltonozhsky; A. G. Zelinsky; N. V. Strilchuk (Ядерна фізика та енергетика)
In the work presented the energy and K-shell internal conversion coefficient for γ-transition with the energy of 112,8 keV in 234Pa were measured. The following estimates for Eγ = 112,790 ± 0,002 keV and aK = 0,220 ± 0,011 have been obtained. The experimental value aK differs by (21 – 23) % from the theoretical one and it can be treated as the demonstration of correlation effects in the internal conversion.